2019
DOI: 10.1097/cji.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Superimposed Clostridium difficile Infection During Checkpoint Inhibitor Immunotherapy-induced Colitis

Abstract: Immunotherapy with checkpoint inhibitors (ICI) is widely used to treat a variety of neoplasms. ICI can induce an immune response against cancer; however, ICI can also induce autoimmunity, an undesirable side effect. Autoimmune colitis is one of the most well-known and troubling side effects of ICI. In this report, we described a series of 5 patients who developed ICI-induced colitis. During the course of this complication, all developed Clostridium difficile infection (CDI). This report described the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In this cohort, the proportion of significant AEs seemed to be higher compared with prior safety data reported in the clinical studies with single-agent ICIs, which may be explained by the differences of the patient population included. ICI-related attribution was not reported for the AEs observed in our study, but patients on immune therapies who often develop autoimmune dermatitis and colitis with superimposed C. difficile infection have also been observed in such cases (19).…”
Section: Discussionmentioning
confidence: 50%
“…In this cohort, the proportion of significant AEs seemed to be higher compared with prior safety data reported in the clinical studies with single-agent ICIs, which may be explained by the differences of the patient population included. ICI-related attribution was not reported for the AEs observed in our study, but patients on immune therapies who often develop autoimmune dermatitis and colitis with superimposed C. difficile infection have also been observed in such cases (19).…”
Section: Discussionmentioning
confidence: 50%
“…Nearly 20%-30% of patients would experience recurrent grade 3 CIC (195,233). In our analysis, 12.5% (4/32) of patients (36,43,50,54) were retreated with the same ICI therapy used before, one of which experienced the recurrence of grade 3 enterocolitis (54). All of these patients who were reintroduced to ICI therapy harbored deteriorated/recurrent CIC outcomes (P = 0.037) (Table 4).…”
Section: Rechallenge and Recurrencementioning
confidence: 80%
“…They found that most of the patients need steroid, while a minority of them required IFX or vedolizumab, regardless of whether in the initial or recurrent episode. Our analysis showed that 25% (8/32) of patients (36,41,43,46,48,54,57) had recurrent ICI-mediated colitis without ICI retreatment, which received subsequent therapy involving probiotics, antidiarrheal drugs, antiviral drugs, steroid, and immunosuppressants. Four cases with CIC finally did not improve or deteriorate after the second treatment (36,41,48,54).…”
Section: Rechallenge and Recurrencementioning
confidence: 87%
See 1 more Smart Citation
“…For instance, 5-Fluorouracil (5-FU) which is commonly used to treat solid cancers has been found to alter the intestinal microbiota [ 30 , 31 ,]. Recently, there have been frequent reports on the association of newer molecular therapies with Clostridioides difficile infection [ 32 ]. In our patient data, we could not retrieve detailed information regarding the chemotherapy/immunotherapy protocols used due to the inaccessibility to patient oncological treatment charts.…”
Section: Discussionmentioning
confidence: 99%